PEMBERDAYAAN KEMITRAAN MASYARAKAT MELALUI INTEGRASI TEKNOLOGI PRODUKSI, MANAJEMEN KEUANGAN, DAN PEMASARAN UNTUK PENGUATAN UMKM TAMBAK IKAN “TARULI” MENUJU KEMANDIRIAN EKONOMI - Napitupulu, Robert; Sihombing, Septiana; Yuspita, Ni Luh Eta; Sihombing, Risna Primauli; Saputra, Benediktus Handaru; Angelika, Vanessa; Christianty, Licia (Jurnal Pengabdian Masyarakat Polmanbabel, 2025)
The Community Partnership Empowerment Program for Strengthening the “Taruli” Fish Pond MSME towards Economic Independence aims to improve production efficiency, enhance business management, and expand market access through the implementation of technology and training. The main problems faced by the partner include high dependency on commercial feed, high production costs, unstructured financial management, limited access to capital, and marketing that still relies on middlemen at low and fluctuating prices. The proposed solutions include the installation of a pellet-making machine and feed ingredient chopper, training on feed formulation using locally available raw materials, assistance in financial record-keeping, preparation of a business plan, and strengthening marketing through branding and digital media. The results achieved show a significant impact on the production aspect, with a reduction in dependence on commercial feed by approximately 40% and production cost efficiency reaching 30–35%. The feed conversion ratio (FCR) has started to improve, while partners’ skills in feed production have significantly increased. In terms of business management, partners have started simple financial record-keeping and prepared a draft business plan, while in the marketing aspect, direct sales to consumers have begun along with the creation of business social media accounts. This program has proven to increase production independence, reduce production costs, and enhance the competitiveness of the MSME. However, several targets such as finalizing branding, securing access to financing, and product diversification still require further mentoring to maximize and sustain the overall impact.